Solar forcing as driver for late Holocene rainfall intensity in the Peruvian Andes - Schittek, Karsten; Wowrek, Jan; Käuffer, Nicolas; Reindel, Markus; Mächtle, Bertil (Quaternary international, 2025)
This study presents a high-resolution palaeoclimate record from sediment cores collected from the siltation area of Laguna Comercocha (LC) in southern Peru, spanning the last 1070 cal years. The primary objective was to investigate climatic variations and environmental changes before, during and after the Little Ice Age (LIA) in the central Andes, with particular emphasis on precipitation patterns and their relation to solar forcing. The extracted core provided a continuous sedimentary archive, offering insights into climate variability on sub-centennial to inter-decadal timescales. The methodology included analysing the sediment cores using X-ray fluorescence (XRF) to measure the concentrations of allogenic elements such as titanium (Ti), silicon (Si), potassium (K), iron (Fe) and calcium (Ca). Ti/coh ratios served as proxy for effective rainfall and runoff from the local catchment. In addition, pollen and non-pollen palynomorphs (NPPs) were identified and quantified to reconstruct past vegetation and climatic conditions. The study revealed that lithogenic input to the LC increased significantly after 1150 cal yr AD, likely due to increased precipitation. In particular, periods of increased lithogenic input were identified during the LIA, corresponding to solar minima and pointing to solar forcing as a major driver of precipitation changes in the central Andes.